Profit and loss allocation among Islamic bank and client partner in equity financing: practice, precepts and alternatives - Sadique, Muhammad Abdurrahman (King Abdulaziz University, 2009)
The profit sharing ratio in equity financed projects is decided by Islamic banks mainly through applying the relevant rate of return on capital. After first determining the return sought by the bank, the remainder of the expected profit is usually taken as the share of the joint partner, and the proportion adopted as the profit sharing ratio. Ideally, the profit sharing ratio should be decided through a mutual process considering the contributions of both partners, with due recognition of the level of liability each had borne. The period, as a factor common to the joint venture, could be redundant. Hence, the profit sharing ratio should be reflective of the capital and labour outlay of both the bank and the client, to the extent possible. In view of the socio-economic function expected of Islamic banks, the method for profit ratio calculation adopted should adequately consider the actual contributions of both the partners. Two bases possible are giving capital and labour of both partners equal weightage, and giving capital a weightage different from labour.